The effectiveness of self-care management in treating heart failure: A scoping review - Alfrina Hany; Ratih Arum Vatmasari (PAGEPress Publications, 2023)
Introduction: Heart failure is a common chronic disease associated with increased mortality and rehospitalization rates. Self-care management provided in various ways is one approach to avoiding the need for rehospitalization by lowering recurrence rates. Therefore, this study aims to determine the most effective self-care management interventions for heart failure patients. Design and Methods: The databases Science Direct, Google Scholar, and PubMed were used to conduct literature reviews over ten years. In September 2021, a full-text article search was conducted using the keywords "Self-Care," "Self-Management," "Intervention," "Heart Failure Patients," and "Randomized Control Trial" in PubMed ScienceDirect and Google Scholar databases. The inclusion and exclusion criteria were determined using the PICOS technique. After the screening, 39 articles met the criteria. Results: Self-care management is provided through education programs, training programs, and the utilization of apps and websites to improve its self-care abilities. Conclusions: Therefore, one way to provide self-care management during the COVID-19 pandemic was through the program's website, which is viewed "remotely" and used to track patient progress.